(untitled) (Physical Education, Health and Social Sciences, 2026)
The objective of this study was to examine the effect of Melia azedarach, commonly known as chinaberry, on the growth, hematological characteristics, and serum immunological parameters of Common carp (Cyprinus carpio). This experimental study involved four groups: a control group fed with a basal diet having no Melia azedarach leaf extract addition, and three experimental groups, T1, T2, and T3, fed with 1%, 2% and 3% of Melia azedarach leaf extract, respectively. Each aquarium contained ten fish. The results obtained at the end of the feeding period indicated that the Common carp fed with diets comprising 1%, 2% and 3% Melia azedarach leaf extract had higher weight gain, SGR percentage, and feed conversion ratio compared to the control group. Hematological analyses revealed that Red blood cell (RBC) count (Control: 2.50×106/µL; T3: 4.15×106/µL) and hemoglobin (Hb) levels (Control: 6.80×µL; T3: 11.20µL) were high. Similarly, immunological parameter were also high in all treatment group i.e. Neutrophil (Control: 80%; T3: 85.5), Lymphocytes (Control: 6%; T2 and T3:8), Monocytes (Control: 3%; T2: 3.9) and Eosinophil (Control: 3%; T3: 2,4) were significantly higher in the treatments groups compare to the control group, suggesting a positive growth and health effect of the plant extract on grass carp. The study concludes that Melia azedarach leaf extract has a positive effect on the growth, hematology, and immunological parameters of common carp, therefore, safe in the current proportion as investigated in this experiment. Also, a cost-effective natural growth promoter and immunity booster being easily available in the local markets of Pakistan, Melia azedarach may as well be included in the diets of common carp in fish hatcheries across the country.